G-CSF treatment for STEMI: final 3-year follow-up of the randomised placebo-controlled STEM-AMI trial. Issue 7 (10th January 2014) - Achilli, Felice; Malafronte, Cristina; Maggiolini, Stefano; Lenatti, Laura; Squadroni, Lidia; Gibelli, Giuseppe; Capogrossi, Maurizio C; Dadone, Viola; Gentile, Francesco; Bassetti, Beatrice; Di Gennaro, Filiberto; Camisasca, Paola; et al.
Abstract : Objective: To assess whether granulocyte colony-stimulating factor (G-CSF) treatment induces a sustained benefit on adverse remodelling in patients with large anterior ST-elevation myocardial infarction (STEMI) and left ventricular (LV) dysfunction after successful reperfusion. Methods: The STEM-AMI Trial was a prospective, placebo-controlled, multicentre study. Sixty consecutive patients with a first anterior STEMI, who underwent primary percutaneous coronary intervention 2–12 h after symptom onset, with LV ejection fraction (LVEF) ≤45% measured by echocardiography within 12 h after successful revascularisation (TIMI flow score ≥2), were randomised 1:1 to G-CSF (5 µg/Kg body weight b.i.d . ) or placebo. Clinical events and Major Adverse Cardiac and Cerebrovascular Event (MACCE) were monitored, and LVEF, LV end-diastolic (LVEDV) and end-systolic (LVESV) volumes, and infarct size were evaluated by MRI at the final 3-year follow-up. Results: Fifty-four patients completed the study, of whom 35 with MRI. No significant differences were found in mortality and MACCE between G-CSF and placebo-treated groups. The 3-year infarct size was not different between groups, whereas LVEDV was significantly lower in G-CSF (n=20) than in placebo (n=15) patients (170.1±8.1 vs 197.2±8.9 mL, respectively; p=0.033 at analysis of covariance). A significant inverse correlation was detected in G-CSF patients between the number of circulating CD34 cells at 30 days after reperfusion and the 3-year absolute and indexed LVEDV (ρ=−0.71, 95% CI −0.90 to −0.30, and ρ=−0.62, −0.86 to −0.14, respectively), or their change over time (r=−0.59, −0.85 to −0.11, and r=−0.55, −0.83 to −0.06, respectively). Conclusions: G-CSF therapy may be beneficial in attenuating ventricular remodelling subsequent to a large anterior STEMI in the long term. No differences have been detected in clinical outcome.